Ion-Exchange and Adsorption Properties of Titania Gels Prepared from Titanous Chloride and Hydrogen Peroxide - Nahed Yacoub; Adham R. Ramadan; Jehane Ragai (Adsorption Science & Technology)
A study was carried out of the uptake of Cu 2+ , Ni 2+ , Co 2+ and Ca 2+ cations by hydrous titanium oxides prepared at different pH values using titanous chloride as the starting material and hydrogen peroxide as the oxidizing agent. Characterization of the oxides was carried out by nitrogen adsorption and infrared studies. The oxides were found to be amphoteric in nature and exhibited an isoelectric point of 6.6. An attempt was made to elucidate the mechanism of cation uptake which does not entail a simple ion-exchange mechanism.